ECONOMIC EFFECTS OF INTENSIFYING PRODUCTION OF MAIN FIELD CROPS - Muncan, Mihajlo (Economics of Agriculture, 2017)
The starting hypothesis of the present study was the assumption that the intensity of production of main feld crops on family farms can be raised to a higher level by rational use of mineral fertilizers as one of the fastest, simplest and economically most rational measures. The determination/resolution to increase the level of intensity of production of main crops in this way has derived from the results of the survey conducted on 75 family farms in Vojvodina, which showed that family farms, despite the performed analysis of soil fertility and received recommendations from the expert agricultural services for optimum application of mineral fertilizers, in most cases (73%) did not respect obtained recommendations. Therefore the aim of this paper is to estimate the economic effects of the intensifying production of main feld crops on family farms through rational use of mineral fertilizers. The obtained results show that the most signifcant economic effects of intensifying production can be achieved on farms of 10-20 ha of arable land.